Penentuan alternatif strategi mitigasi risiko kecelakaan kerja dengan metode analytic network process di PT XYZ - Fitri Febri Anandra; Rahayu Gama Harta Nugraha Nur (Journal Industrial Servicess, 2020)
Work health and safety (WHS) issues in the construction sector in Indonesia still require better attention considering that this sector has a very high risk of work accidents. To minimize the risk of work accidents, a risk mitigation strategy is needed as part of decision making. There are many factors that can trigger the cause of work accidents. This study aims to determine the potential causes of the risk of workplace accidents and determine their mitigation strategies. The main process carried out is the determination of the criteria that cause occupational accidents and the analysis of the determination of work accident risk mitigation strategies. Given the interrelationships between criteria, sub-criteria and alternatives, the method used is the Analytic Network Process (ANP). The results showed that the cause of WHS risk in the construction sector was dominated by environmental criteria of 0.254; followed by material criteria of 0.207; human criteria of 0.138; machine criteria of 0.125 and method criteria of 0.058. While the main ranking in the sub-criteria is the temperature of the production room which has a value of 0.129 and the most recent ranking is the material placement method which has a value of 0.019. From these results, it can be seen that there is a relationship between environmental criteria and the production room sub- criteria. In the process of determining the risk mitigation strategy as part of decision making, an alternative strategy that has the highest weight is the addition of air circulation with a weight of 30.6%.